English Corporate Governance Implementation on Related Party Transactions in Indonesia - Ade Raynaldi Harahap; Elisabeth Penti Kurniawati; Ahmad Maulin Naufa (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
This research aims to examine the effect of corporate governance implementation on related party transactions (RPT) in Indonesian commercial banks. RPT is proxied by two variables-debt and receivables. This study multiple regression methods to analyze the relationship. We found that the corporate governance (CG) has no significant effect on debt with related parties in the banking sector. Then, CG also does not have a significant effect on receivables from related parties in the banking sector. Those results indicate that albeit the government and the company implement the CG on Indonesian commercial banks, it did provide benefit to alleviate RPT. RPT itself lead the drawbacks to the company.